ANALISIS PENGARUH BOOK-TAX DIFFERENCES TERHADAP PERSISTENSI LABA - Wijayanti, Handayani Tri (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2010)
This study aims to obtain empirical evidence about the role of differences between accounting income and taxable income (book-tax differences) of earnings one period ahead. In addition this study aims to test whether the difference between accounting earnings and taxable income will also affect investors assessment of earnings persistence in the future. The hypothesis proposed is: (1) firms with large book-tax differences has a lower accounting earnings persistence than firms with small book-tax differences, (2) firms with large book-tax differences has a persistence of accrual components is lower than companies with small book-tax differences. The samples used were 40 companies listed in Indonesia Stock Exchange (IDX), and publish audited financial statements are consistent in the year 2000-2005. The data was collected using purposive sampling. The statistical methods used are panel data regression. The results showed that firms with large large book-tax differences of having lower earnings persistence than firms with small large book-tax differences. However, the low persistence of earnings is not statistically proven due to the accrual component. Investors have not been able to distinguish the information contained in accruals and cash flow component in determining the persistence of earnings. Information about the size of the large book-tax differences contained in accruals component can not affect investors assessment of earnings persistence in the future